PARAMETRIC SPIN-VALVE EFFECT IN THE NB/HO STRUCTURES - V. N. Kushnir (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
In the formalism of equations of the diffusive limit of the microscopic theory of superconductivity, the results of experimental investigations of the spin-valve effect in epitaxial Nb/Ho structures are explained. The mechanism of the “quasi-metal” behavior of their critical dependences is established.